Temporal transcriptomic profiling of pulmonary thromboembolism reveals persistent NETosis- and ferroptosis-associated gene signatures and enhanced thrombolysis with adjunctive DNase I - Jialun Chen; Lingshan Chao; Siqin Han; Zaixing Jia; Weihua Chen; Zhenwei Liu; Jingwen Li; Xixin Yan (PLoS ONE, 2026)
Objective To investigate the dynamic pathophysiology of pulmonary thromboembolism (PTE), focusing on the roles of neutrophil extracellular traps (NETs) and ferroptosis, and to evaluate intravenous DNase I as an adjunct to recombinant tissue plasminogen activator (rt-PA). Methods A rabbit autologous thrombus PTE model was established using 62 animals for the time-course and therapeutic-intervention experiments. Disease progression was assessed at days 1, 3, 7, and 14 using histology (collagen volume fraction, CVF), serology (e.g., MPO-DNA, PAI-1, t-PA), and RNA-sequencing. Bioinformatics identified NETs- and ferroptosis-related genes, validated by qRT-PCR. Based on peak NETs activity at day 7, an intervention study (n = 12) compared rt-PA monotherapy versus rt-PA plus intravenous DNase I, with outcomes assessed 7 days post-treatment. In addition, an independent four-group mechanistic validation cohort (Control, PTE, PTE + DNase I, and PTE + ferrostatin-1 [Fer-1]; n = 5 per group) was used to evaluate NETs, TLR9, phospho-p65, total p65, and GPX4 by ELISA and qRT-PCR. Results The PTE model demonstrated progressive pulmonary fibrosis (increasing CVF, P < 0.05) and a sustained hypofibrinolytic state. The NETs marker MPO-DNA peaked at day 7 (P < 0.01). Transcriptomic analysis revealed persistent activation of neutrophil degranulation and iron homeostasis pathways, with early ferroptosis and late collagen metabolism enrichment. Therapeutically, rt-PA plus DNase I was superior to rt-PA alone, yielding greater improvements in CVF (P < 0.01), pulmonary artery acceleration time (P < 0.01), oxygen saturation (P < 0.001), left ventricular function (P < 0.05), and serological markers of endothelial injury and cardiac strain (P < 0.05). In the independent validation cohort, PTE increased circulating MPO-DNA complexes, TLR9, phospho-p65 signaling, and the phospho-p65/total p65 ratio while decreasing GPX4; DNase I attenuated upstream MPO-DNA-associated changes in TLR9-NF-kB signaling, whereas Fer-1 more prominently restored GPX4 expression. Conclusion These findings suggest sustained NETs-associated activity and ferroptosis-related processes during PTE progression, identify stage-specific molecular signatures, and support DNase I as a potential adjunct to enhance thrombolysis, while mechanistic relationships require further validation.